FUTURISTIC INTERPRETATION OF SINGER LICENSING TO SONGWRITERS IN THE ENFORCEMENT OF ROYALTY RIGHTS BY LMKN (NATIONAL COLLECTIVE MANAGEMENT INSTITUTION) IN INDONESIA - Muhammad Rifzal Alief Ramadhan; Desta Apner Ventura (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research aims to analyze the role and authority of the National Collective Management Institute (LMKN) in regulating and enforcing licensing and royalty distribution between singers and songwriters. In addition, this study also examines a futuristic interpretation that can be applied in the licensing system between singers and songwriters to strengthen the enforcement of royalty rights in the future in accordance with Article 34 of Law Number 28 of 2014 on Copyright, which states that in cases where a creation is designed by one person and realized and executed by another under the leadership and supervision of the designer, the designer is considered the creator. The problem is the legal uncertainty felt by performers regarding the use of copyrighted works in concerts or performances without direct permission from the song creators. The exception for direct permission is for those who request that the use of their works in commercial performances does not require direct permission from the song creators, as long as royalties are still paid. The obligation to pay royalties must contain legal certainty that the obligation to pay royalties becomes the responsibility of the event organizer, unless there is a different agreement between the parties involved, as royalty payments are a civil matter according to the content of Article 1320 of the Civil Code. In conclusion, the potential for abuse of power and arbitrariness due to the lack of a clear control mechanism over LMKN creates the potential for abuse of authority in the management of royalties, even arbitrariness. The duality of authority with Collective Management Institutions (LMK). Government Regulation no. 56 of 2021 concerning the Management of Copyright Royalties for Songs and/or Music based on Law No. 28 of 2014 concerning Copyright grants LMKN the authority to collect and distribute royalties. This authority is the same as that of LMK. This means that one authority is granted to two different institutions.